Researcher’s Autobiographical Narrative as a Tool Used in Reflective Research: Performative Autoethnography as Cognitive and Interpretive Challenge - Golonka-Legut, Joanna (Narrative Works, 2026)
The article addresses the issue of understanding and intentional use of researcher’s autobiographical narrative in the social research on the example of performative autoethnography. The reference point to reflection is a research project conducted as part of an initiative titled “Microworlds of Maternity”. The research involved a researcher (the author of the research) telling and analyzing her own story in the form of a short video. The researcher’s autobiographical narrative is treated as a reflective research tool. Then, the so called external investigator (the author of this article) further analyzes the video material. Interpretation of the video provides insight not only into the way the researcher’s narrative is used in the research process but also into the way it is transformed into a visual story (knowledge about maternity experience). Such an approach provides an opportunity to explore the practice of joining together interpretation perspectives in the form of investigator triangulation and allows to present interactions between the narrative and its interpretation – in the context of the researcher herself and in the dialogue with the other investigator. As a result, performative autoethnography is presented both as a research approach and a space for multiple voice interpretation and reflection on the limits of cognition in the scientific research. Reflections presented herein focus on understanding the research process as a learning situation for: researchers, respondents and recipients. The example recalled in the paper is a study conducted in the area of educational research.